MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA KULIAH BAHASA INGGRIS - Miftahul Farid Mochamad Ahyar; Nurul Frijuniarsi; Fitri Senny Hapsari (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2022)
The implementation of quality education and learning is inextricably linked to the role of educators (teachers/lecturers) who master teaching materials and an educator's ability to apply learning models appropriate for the classroom environment. The use of learning models can be used to improve the quality of learning, which can have an impact on learning outcomes. Students who like challenges, socialism, and free expression and have begun to be trained to think logically are very suitable for the problem-based learning principle model to improve learning outcomes in English courses that are not a significant subject and are less appealing to students. Classroom Action Research is used to implement the PBL learning model over two cycles. It is known that PBL was successfully implemented for 70 students, with a significant increase from the average student score before implementation, namely 65, to 75 in the first cycle and increasing to 80 in the second cycle.